Midwifery Perspectives on Maternal Nutritional Barriers in Stunting-Prone Areas: A Qualitative Thematic Analysis - Yeni Yeni Fitrianingsih; Nina Nirmaya Mariani; Suratmi Suratmi; Priyo Sulistiyono (Journal of Nutrition Explorations, 2026)
Inadequate maternal nutrition during pregnancy directly triggers chronic malnutrition and stunting, severely impacting fetal development and long-term cognitive growth. This study aims to explore the socioeconomic and cultural barriers to adequate nutritional intake among pregnant women in stunting-prone urban areas and to identify integrated solutions. A convergent parallel mixed-methods design was conducted in Cirebon City, Indonesia. Quantitative data from 42 pregnant women selected via purposive sampling a sample size adequate for thematic saturation in this localized context were collected via questionnaires and analyzed using descriptive statistics. Concurrently, qualitative insights were gathered through semi-structured in-depth interviews and analyzed using inductive thematic analysis. Economic constraints emerged as the primary barrier, with 64.3% of families living below the regional minimum wage. Cultural traditions, including specific food taboos and early marriage, further compromised dietary quality. While maternal nutritional awareness was moderate (71.4%), the quality of counselling provided by local health workers remained suboptimal and irregular. Maternal malnutrition in stunting-prone urban areas is deeply rooted in structural economic limitations and reinforced by cultural practices. Addressing this requires localized policy interventions that combine economic safety nets with culturally tailored nutritional education from healthcare providers.